A neonatal small left colon syndrome of nondiabetic mother - Usama Qumsieh; Mohannad S. Jaber; Weaam Emran; Insaf Abdelghani; Fatima Manasra; Nancy Ahmad; Baraa Shawar (Elsevier, 2023)
Background: Neonatal small left colon syndrome (NSLCS) is a rare condition that cause a clinical picture of large bowel obstruction. The obstruction typically arises from the descending colon distal to the splenic flexure. Which is clinically characterized by failure to pass meconium and abdominal distension within 48h after birth and is usually followed by bilious vomiting and feeding intolerance.The incidence of NSLCS is increased in infants of diabetic mother, pathology of which is not fully understood. Case presentation: We describe a case of a 48 hours old neonatal male presenting with vomiting of bilious color after each breast feeding, associated with abdominal distention and failure to pass meconium. His mother had free antenatal history.The patient was admitted to our neonatal intensive care unit (NICU) and kept NPO for further investigation and underwent fluoroscopic contrast enema. The contrast enema outlined the whole length of the large colon, which was diffusely small in caliber till the transverse colon where a transitional zone was seen proximal to which the colon was largely dilated, findings consistent of micro-colon.The patient passed large amount of meconium spontaneously after the lower GI contrast study was performed.Decision for rectal biopsy was then made. And the pathology report showed presence of ganglion cells.Following the study, the patient started passing spontaneous bowel movements, his diet was then advanced without issues and he was discharged in good general condition and remained doing well and symptoms-free throughout the follow up period of 4 years.No significant prenatal, natal or postnatal history was found for the baby, the mother was not diabetic nor had gestational diabetes during the pregnancy and had normal prenatal obstetric visits, HbA1C was also normal for the mother. Conclusion: NSLCS is one of the common causes of neonatal period bowel obstruction. It should be suspected in infants of diabetic mothers and usually diagnosed by a LGI contrast study. In the study, the rectum should be of regular width, the rectosigmoid ratio should be normal thus differentiating it from the finds in Hirschprung's disease. A transitional zone is classically seen at the splenic flexure.In NSLCS the enema is both diagnostic and therapeutic and can be repeated if necessary.This case is unique as the patient did have NSLCS, however, there was no evidence whatsoever of maternal diabetes or gestational diabetes making it unique.